THE RELATIONSHIPS AMONG LEARNING INDEPENDENCE, REASONING ABILITY, AND LEARNING ENVIRONMENT AT HOME WITH STUDENTS MATHEMATICS LEARNING OUTCOMES IN CLASS XI TKJ OF EVEN SEMESTER IN SMK NEGERI 1 PLERET BANTUL - Nining Apriani; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Learning mathematics is still considered difficult by most students, so the impact on learning outcomes. The lack of seriousness and independence of learning, reasoning ability is still low, and not all families have an adequate learning environment and conducive are several factors that may affect learning. Therefore, this study was conducted in order to determine whether or not a positive and significant between the relationship among learning independence, reasoning ability and learning environment at home with students mathematics learning outcomes in class XI TKJ of even semester in SMK Negeri 1 Pleret Bantul Regency at Academic Year 2015/2016. The population of this research was all students of class XI TKJ of even semester in SMK Negeri 1 Pleret Bantul in the academic year 2015/2016 consisting of 2 classes. As a sample class was class XI TKJ B by random sampling technique to the class. The data collection technique was performed by a method of testing and questionnaires. The questionnaire method used collection data learning independence and learning environment at home, as well as the test method used collection data on reasoning ability and mathematics learning the result of the student. Test data analysis requirements using the test for normality, independent, and the test for linearity. Data analysis for hypothesis testing using correlation analysis and linear regression analysis. The research result showed that there was a significant positive correlation between learning independence, reasoning ability and learning environment at home with students mathematics learning outcomes with  > . Multiple correlation coefficient (R2) of  with a regression equation  with the relative contribution of ( ) = 34,44%, ( ) = 8,64%, ( ) = 56,91%, with coefficient of determination  was  and effective contribution , , dan .